Studi Kasus Penggunaan Obat Tradisional Daun Jarak Merah (Jatropha gossypifolia L) sebagai Obat Anti Malaria pada Mahasiswa dan Alumni Teknologi Laboratorium Medis - Irfan H. Arif; Zulkifli I. Tuara; Asmin Lukman (Peneliti.net, 2021)
This research is a survey research with a survey method for ages 18-26 years with a profession as a Health Analyst, intending to qualitatively describe the use of red jatropha leaves as traditional medicine. Charging the respondent's knowledge of the use of traditional medicine shows that 55% do not know when compared to those who know only 45% of respondents who know traditional anti-malarial medicine 55% of them choose red castor plants while others choose other traditional medicines. These results indicate that the average respondent has a more negative response to the supervision of the use of red jatropha leaves as an anti-malarial drug, but the difference is not that far, it's 6% of the sample chooses between using traditional medicine and modern medicine